The Oxford guide to library research - Mann, Thomas 1948- (Oxford University Press, 2015)
"The information world has undergone drastic changes since the publication of the 3rd edition of The Oxford Guide to Library Research in 2005, and Thomas Mann, a veteran reference librarian at the Library of Congress, has extensively revised his text to reflect those changes. This book will answer two basic questions: First, what is the extent of the significant research resources you will you miss if you confine your research entirely, or even primarily, to sources available on the open Internet? Second, if you are trying to get a reasonably good overview of the literature on a particular topic, rather than just "something quickly" on it, what are the several alternative methods of subject searching--which are not available on the Web--that are usually much more efficient for that purpose than typing keywords into a blank search box, with the results displayed by relevance-ranking computer algorithms? This book shows researchers how to do comprehensive research on any topic. It explains the variety of search mechanisms available, so that the researcher can have the reasonable confidence that s/he has not overlooked something important. This includes not just lists of resources, but discussions of the ways to search within them: how to find the best search terms, how to combine the terms, and how to make the databases (and other sources) show relevant material even when you don't know how to specify the best search terms in advance. The book's overall structuring by nine methods of searching that are applicable in any subject area, rather than by subjects or by types of literature, is unique among guides to research. Also unique is the range and variety of concrete examples of what to do--and of what not to do. The book is not "about" the Internet: it is about the best alternatives to the Internet--the sources that are not on the open Web to begin with, that can be found only through research libraries and that are more than ever necessary for any kind of substantive scholarly research. More than any other research guide available, this book directly addresses and provides solutions to the serious problems outlined in recent studies documenting the profound lack of research skills possessed by today's 'digital natives.'"-- Provided by publisher.